Glycosylation of canine tetherin is essential for its antiviral activity against H3N2 canine influenza virus - Xu, Liang; Hou, Yuwen; Liu, Shizhe; Dai, Yixin; Ou, Jiajun; Ye, Shaotang; Wang, Zhen; Lu, Gang; Li, Shoujun (Frontiers in Veterinary Science, 2025)
Tetherin is an interferon-induced-expressing transmembrane protein that utilizes a unique topology to restrict the release of enveloped viruses from the surface of the cell membrane. N-linked glycosylation plays an important role in protein post-translational modifications. To investigate the role of glycosylation in the antiviral activity of canine tetherin, its potential glycosylation sites were predicted and mutated, and the effects of glycosylation site mutations or treatment with a glycosylation inhibitor on the ability of canine tetherin to restrict H3N2 canine influenza virus (CIV) replication were examined. Mutations in the glycosylation sites of canine tetherin (N72A, N99A, and N72,99A) lead to changes in its intracellular distribution and weakened or even lost antiviral activity against H3N2 CIV. Similarly, the subcellular localization of tetherin after tunicamycin treatment was altered, and its antiviral activity was weakened. Colocalization analysis revealed that the colocalization of canine tetherin and H3N2 CIV protein was weakened under the condition of impaired glycosylation. These results indicate that canine tetherin maintains its localization in the cell membrane through glycosylation and exerts its antiviral activity. This study provides new insights into the antiviral mechanisms of host restriction factors and offers a theoretical basis for developing small-molecule anti-influenza strategies targeting glycosylation modifications.